Reviewing Constitutional Court Decision Number 91/PUU-XVIII/2020 Regarding Formal Review of Job Creation Act: a Progressive Law Perspective - Satria Rangga Putra; Sujatmiko Sujatmiko (Law and Human Rights Policy Strategy Agency, Ministry of Law and Human Rights of The Repub, 2022)
The Constitutional Court Decision Number 91/PUU-XVIII/2020 states that the Job Creation Act has a formal defect and must be corrected within 2 (two) years since the decision was pronounced. The a quo decision created a discourse in the community regarding the enforcement status of the Job Creation Act. This paper tried to review constructively using the perspective of progressive law and judicial proportionality in finding solutions and balances. This paper used a normative juridical research method, with a conceptual, case, and legislation approach. Progressive law in Satjipto Rahardjo's perspective has four criteria. The first has a big goal in the form of human welfare and happiness. Second, contains very good human moral content. Third, progressive law is a